THE INFLUENCE OF RUPIAH, INCREASE OF WAGES AND ELECTRICITY ON WORKING CAPITAL AND PROFITABILITY - Maman Sumantri; Bambang Juanda; Dwi Rachmina (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The purpose of the research was to find out the effects of rupiah exchange per US dollar, and increase of wages and electricity on the ratio of net working capital and profitability. Descriptive methodology using case-study approach was used in PT XYZ as a producer of sewing thread. Secondary data were collected from January 2009 to June 2014. Monthly data of financial ratios consisting of liquidity ratio, activity ratio, and profitability ratio was analyzed with multiple regressions using Minitab 16. The results showed that rupiah impairment per US dollar could lower the ratio of net working capital and profitability. The increase of wages and electricity would increase the ratio of net working capital, but fortunately it would also increase profitability due to the increase of employees’ productivity and efficient use of electricity. All the free variables insignificantly affect net working capital and profitability. The study also showed that the impairment of rupiah exchange and working capital variables that are measured by receivables age, inventory age, and loan age could influence return on asset. The impairment of rupiah exchange rate, receivables age, and inventory age had a negative impact on the return on asset, while loan age had a positive impact on the return on asset. The impairment of rupiah exchange rate, receivables age, and inventory age had a significant influence on the return on asset so that the company’s management must focus more on anticipating rupiah exchange fluctuation, and management of accounts receivables and inventory. Keywords: net working capital, liquidity ratio, profitability ratio, multiple regression analysesAbstrakTujuan dari penelitian adalah untuk melihat dampak dari kurs Rupiah per USD, kenaikan biaya upah dan listrik terhadap rasio modal kerja bersih dan profitabilitas.  Metode deskriptif dengan pendekatan studi kasus dilakukan pada perusahan PT XYZ sebagai produsen benang jahit.  Data sekunder dikumpulkan dari bulan Januari 2009 sampai dengan Juni 2014 dan data bulanan rasio keuangan yang terdiri dari rasio likuiditas, rasio aktivitas, dan rasio profitabilitas dianalisis dengan regresi berganda menggunakan Minitab 16.  Hasil penelitian menunjukkan bahwa pelemahan Rupiah terhadap USD akan menurunkan rasio modal kerja bersih dan profitabilitas.  Kenaikan biaya gaji dan listrik akan meningkatkan rasio modal kerja bersih, namun secara menguntungkan meningkatkan profitabilitas akibat dari peningkatan produktivitas karyawan dan efisiensi pemakaian listrik.  Semua variabel bebas tersebut secara tidak signifikan mempengaruhi modal kerja bersih dan profitabilitas.  Studi juga menunjukan bahwa pelemahan kurs Rupiah dan variabel modal kerja yang diukur dengan umur piutang, umur persediaan, dan umur hutang dapat mempengaruhi return on asset.  Pelemahan nilai tukar Rupiah, umur piutang dan persediaan mempunyai pengaruh negatif terhadap return on asset, dan umur hutang mempunyai pengaruh positif terhadap return on asset.  Pelemahan nilai tukar Rupiah, umur piutang usaha dan persediaan mempunyai pengaruh yang signifikan terhadap return on asset sehingga manajemen perusahaan harus lebih fokus dalam mengantisipasi fluktuasi kurs Rupiah, dan manajemen piutang dan persediaan.Kata kunci:   modal kerja bersih, rasio keuangan, rasio likuiditas, rasio profitabilitas, analisis regresi berganda